Static Analysis Meets Artificial Intelligence: A Hybrid Framework for PHP Vulnerability Detection Using DeepSeek LLM and Machine Learning (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The fast adoption of Large Language Models (LLMs) for code generation has revolutionised the process of constructing online applications; nevertheless, the security implications of AI-generated PHP code are still not fully understood. Combining static analysis, machine learning, and LLM-driven intelligence, this research provides a comprehensive hybrid vulnerability detection system that can identify security weaknesses in PHP web applications. The method is designed to identify vulnerabilities in PHP web applications. Utilising eleven different vulnerability categories that are connected to the CWE and OWASP Top 10 standards, our system is more secure. In addition, a trainable Random Forest classifier that utilises TF-IDF vectorisation is utilised, and DeepSeek LLM is incorporated for the purpose of providing intelligent explanations and remediation guidance. We demonstrate that the framework finds 15 vulnerabilities across 8 CWE categories from a single configuration file by conducting exhaustive assessments on vulnerable PHP code samples. As a result, the framework achieves a Security Score of 62%. A total of eight medium vulnerabilities, two critical vulnerabilities (SQL Injection), four high vulnerabilities (Hardcoded Credentials, Authentication Bypass, and Broken Access Control), and one low vulnerability were discovered by the static analysis engine. With the help of DeepSeek, the neuro-symbolic pattern generating component was able to attain an average accuracy of 76.6% while simultaneously lowering the amount of time required to produce patterns from weeks to hours. Authentication Security (0%-27% coverage) and HTTP Security Headers (0% coverage) were found to have major gaps in coverage due to the risk assessment that was conducted across five different LLM models. The fact that the whole open-source Streamlit application provides interactive vulnerability reporting along with the ability to export in both JSON and HTML demonstrates that hybrid AI-driven static analysis is an essential tool in contemporary DevSecOps workflows.